Illustrating and Designing Quranic Imagery - Almenoar, Lubna (Journal of the American Academy of Special Education Professionals, 2009)
Selected verses from Abdullah Yusuf Ali’s English language translation of the meaning of the Quran have been used as a literary text to teach both descriptive and figurative imagery (including similes, metaphors and symbols) to students at the undergraduate level in an Islamic institution. The technique–Illustrating and Designing for teaching imagery has been selected to accommodate the text. The group of students was taught imagery using one technique covering 2 class sessions. Assignments were given to derive data for the evaluation of the level of understanding of the lessons on imagery. An analysis of the data from the assignments shows a high level of understanding of the lessons on imagery by the students.